2001
DOI: 10.1186/1471-2377-1-7
|View full text |Cite
|
Sign up to set email alerts
|

Weather conditions and Bell's palsy: five-year study and review of the literature

Abstract: Background: Climatic or meteorological condition changes have been implicated in the pathogenesis of Bell's palsy (BP). We evaluate the influence of meteorological parameters, such as temperature, humidity, and atmospheric pressure, and their variation and covariation on the incidence of BP and present a review of the literature on the effect of meteorological conditions on facial nerve function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 29 publications
2
21
0
2
Order By: Relevance
“…Experimental findings supported the hypothesis of the etiopathogenetic relevance of low temperatures, which might be related to a higher incidence of BP during the colder period of the year [11]. However, the association of lower temperatures with a higher incidence of BP remains a matter of debate, since recent studies from Mediterranean countries reported conflicting findings [12, 13]. …”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Experimental findings supported the hypothesis of the etiopathogenetic relevance of low temperatures, which might be related to a higher incidence of BP during the colder period of the year [11]. However, the association of lower temperatures with a higher incidence of BP remains a matter of debate, since recent studies from Mediterranean countries reported conflicting findings [12, 13]. …”
Section: Introductionsupporting
confidence: 59%
“…Recently, a Spanish group reported an association between temperature and BP incidence, while a similar relation to other meteorological parameters could not be established [12]. Just 1 year earlier, a group from the northwest of Greece had failed to identify any relation between BP incidence and weather conditions, including temperature [13]. …”
Section: Discussionmentioning
confidence: 99%
“…There have been conflicting results in these studies. [8][9][10][11] Although many previous studies have commented on different demographic parameters in facial palsy patients, none of them have commented over the predominant side of facial nerve lesion in facial palsy males and female patients. 9,[12][13][14][15][16] Hence, we planned to retrospectively analyse the predominant side of affection in facial palsy male and female patients.…”
Section: Introductionmentioning
confidence: 99%
“…Supposedly, combination of certain, yet not fully elucidated, ideal climatic conditions may facilitate HSV-1 primary infection or render human tissues more vulnerable to HSV-1 reactivation [11]. First of all, there is a well-established correlation between cold, winter seasons and the observed number of cases [10,11,12,13,14]. An obvious explanation should attribute the effect in the existence of an inverse association between the risk for BP and the absolute values of temperature [2,15].…”
Section: Introductionmentioning
confidence: 99%
“…The most dominant candidates, considered as probable causative factors, include neurotropic viral infections and especially herpes simplex virus type-1 (HSV-1) infection or reactivation, dysregulations of the regional vascular milieu, hypertension, diabetes mellitus (DM) and autoimmune events that usually follow vaccination [6,7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%